Reasons for Removal of Titanium Hardware in Postoperative Patients with Maxillofacial Trauma - Dildar, Zahid; Ishaq, Muhammad; Khan, Ali Akhtar; Khan, Shafi Ullah; Bukhari, Syed Junaid Hussain; Mahmood, Tariq (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the reasons for removing titanium hardware (mini plates, microplates, and titanium screws) in postoperative patients with maxillofacial trauma. Study Design: Prospective longitudinal study. Place and Duration of Study: Armed Forces Institute of Dentistry Rawalpindi, Pakistan from Mar to Dec 2023. Methodology: A total number of Fifty-one (n=51) patients reported to the Oral Surgery Department of the Armed Forces Institute of Dentistry for hardware removal previously treated with maxillofacial trauma. After following inclusion and exclusion criteria, consecutive sampling was performed. Reasons for hardware removal were evaluated and recorded. Results: Out of a total of fifty-one individuals, 41(80.3%) were male and 10(19.7%) were females. Of 51 patients, 18(35.2%) reported the complaint of pus discharge as their main reason for seeking expert opinion. In 24(47%) patients, elective hardware removal was performed due to the patient’s demands. Meanwhile, 4(7.8%) patients reported the chief complaint of experiencing pain and unpleasant sensations. Hardware palpability was another factor reported by 5(9.8%) of the patients for hardware removal. Conclusion: The patient’s request and infections were the leading causes of the plates and screws removal. The plate removal usually took place 6 to 12 months after initial surgery, and the mandible was the most often region from where these mini plates and screws were removed.